POLA PENETAPAN KADER BAKAL CALON KEPALA DAERAH DARI PARTAI POLITIK NASIONAL - Welasari, Welasari (LPPM UNAIM, 2025)
The purpose of this research is the Patterns of Establishing Prospective Regional Head Cadres from National Political Parties. This research is classified as a desk study and a type of qualitative research. Qualitative research involves a deeper exploration of a phenomenon. Data collection and data analysis are carried out through literature study and the analysis is conducted through literature review. Literature study is a research method that involves collecting, reviewing, and evaluating the results of previous research relevant to the research theme. Literature sources are obtained by searching for articles from reputable journals on Sinta and Google Scholar.That political parties often involve artists as cadres who advance to become political officials, adding value in gaining votes. An artist, in terms of value, has the value of popularity because in media television screen, although they are still far from political experience and have not contributed much talent in building society. Political parties in winning votes adopt a pragmatic pattern by involving artists as candidates who run for political office to add value in gaining votes. Therefore, in determining candidates for political office in regional leadership roles from political parties seated in the DPR RI, most of the time it is done based on several factors, including the basis of party sympathizers who have electability in terms of popularity, not based on performance, the authority of party leaders in their determination based on closeness and kinship, personal relationships that are not fully based on popularity in society, and not fully based on civil service reform recruitment processes that rely on capacity and loyalty. Because this research is desk study in nature, it is recommended to conduct field research.